The Characterization of Salt Level in Mango Fruit Through Principle of Refraction Index - Ilhami, Fasih Bintang; Budiyanto, Mohammad (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
The characterization of salt levels in fruits with simple techniques still has several challenges to determine. Herein, we successfully present a simple breakthrough to resolve of purity or concentration of a substance by the principle of refraction index with a refractometer. The resulting experiments by mango fruit extracts showed refractive index is produced in NaCl solution at a concentration of 0.1 M; 0.2M; 0.5M; 1 M; 2 M by 1004; 1009; 1016.3; 1017.3; 1058, respectively. More importantly, the highest refractive index produced in mango fruit extract is owned by Manalagi mango with a refractive index of 1047.3, followed by Arum Manis mango with 1041, Banjarnegara mango with 1030, Gadung mango with 1023.3, and Raw mango with 1015,3. Thus, the higher the concentration of the solution would the greater the refractive index produced due to refractive index is inversely proportional to the speed of light in the solution. Therefore, this is a simple technique that can be used to determine salt levels in fruits and allow to select healthy fruit for intake by our body.